Pengembangan Aplikasi Holiyay untuk Perencanaan Liburan Sesuai Anggaran - Natanael Yohanes Gunawan; Hansen Gunawan; Ivan Cornelius Saputra; Putu Crysta Lovita Atmaja; Cynthia Antoni; Lifia Yola Febrianti (Jurnal Sains dan Teknologi, 2023)
Many people aspire to go on vacations, but their wishes often go unfulfilled due to the difficulty of managing the required budget for the trip. Additionally, they encounter challenges in selecting a holiday destination because well-known tourist spots tend to be crowded with visitors, leading to a less comfortable experience. These issues have sparked the interest of a research team in developing an application to address these concerns. The application is designed based on feedback obtained from a survey conducted by the research team. After processing and analyzing the survey results, the team has conceptualized an application called "Holiyay" to assist users in planning vacations within their predetermined budgets. The suggested travel destinations provided by the application are guaranteed to meet quality standards, ensuring a pleasant experience for users. To enhance the comfort of users during their vacations, the application will also offer the services of a guide called "Holiguide" to accompany them. In order to ensure security for both users and the application, a QR code will be provided to users when they book their vacation packages. This QR code will be scanned by the Holiguide to verify the identity of both parties, confirming that they are the designated user and guide provided by the application.